2021
DOI: 10.1016/j.scs.2020.102627
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic determinants of COVID-19 incidence rates in Oman: Geospatial modelling using multiscale geographically weighted regression (MGWR)

Abstract: Highlights The effects of sociodemographic determinants on COVID-19 incidence were spatially modelled. 4 out of 12 sociodemographic variables were influential predictors of COVID-19 incidence rates. MGWR model explained 71% of the spatial variations of COVID-19 incidence rate. Spatial modelling of COVID-19 can be used to guide vital preventative and mitigation measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
95
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(124 citation statements)
references
References 51 publications
7
95
0
3
Order By: Relevance
“…Mollalo et al (2020) investigated county-level variations of disease incidence across the continental United States, compiling environmental, socioeconomic, topographic, and demographic variables that could explain the spatial variability of disease incidence, including the percentage of older adults. Similar studies were carried by Mansour, Al Kindi, Al-Said, Al-Said & Atkinson (2021) in Oman, where they also concluded that an increase in the number of the elderly is associated with an increased rate of disease incidence. Páez et al (2020) investigated the influence of environmental (meteorological) factors, coupled with economic and demographic control variables, on the progression of the incidence of COVID-19 in the coterminous provinces in Spain, demonstrating that population density and percentage of older adults displayed strong associations with incidence of COVID-19.…”
Section: Introductionsupporting
confidence: 71%
“…Mollalo et al (2020) investigated county-level variations of disease incidence across the continental United States, compiling environmental, socioeconomic, topographic, and demographic variables that could explain the spatial variability of disease incidence, including the percentage of older adults. Similar studies were carried by Mansour, Al Kindi, Al-Said, Al-Said & Atkinson (2021) in Oman, where they also concluded that an increase in the number of the elderly is associated with an increased rate of disease incidence. Páez et al (2020) investigated the influence of environmental (meteorological) factors, coupled with economic and demographic control variables, on the progression of the incidence of COVID-19 in the coterminous provinces in Spain, demonstrating that population density and percentage of older adults displayed strong associations with incidence of COVID-19.…”
Section: Introductionsupporting
confidence: 71%
“…These findings are in line with other relevant studies. Positive associations were observed between percent of black population, older population, and COVID-19 mortality ( Hu, Roberts, Azevedo, & Milner, 2021 ) ( Mansour, Al Kindi, Al-Said, Al-Said, & Atkinson, 2021 ). Finally, compared to metropolitan counties, nonmetropolitan counties have significantly greater mortality rates ( Table 2 ).…”
Section: Discussion and Synthesismentioning
confidence: 99%
“… 1 Only few papers to date examined spatial heterogeneity in COVID-19 spread and mortality ( Sannigrahi, Pilla, Basu, Basu, & Molter, 2020 ; Li, Ma, & Zhang, 2021 ; Mansour et al, 2021 ). Using spatial models, Li et al 2021 and Mansour et al, 2021 focused on the sociodemographic determinants of COVID-19 spread/infection in China and Oman, respectively.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, models based on dynamic systems have been at the forefront in terms of variety and application ( Dimitrov & Meyers, 2014 ; Rainisch et al, 2020 ). However, in the last two decades, thanks to extensive advances in the computational power of computers and machine learning techniques, network-based approaches ( Sharkey, 2011 ; Feng et al, 2020 ; Castañeda et al, 2021 ; Mansour et al, 2021 ) and agent-based tracing ( Marini et al, 2020 ) have found a special place.…”
Section: Introductionmentioning
confidence: 99%